PROFESIONALISME REPORTER DAN JURU KAMERA TV (Lembaga Penerbitan Universitas Esa Unggul, 2018)
AbstrakReporters and cameramen in TV news coverage are professional workers. Even though the position is different, both must be able to go along in line. They may not show their